Shear strengthening of RC beams using FRCM system made with industrial wastes. (February 2023) - Ramezani, Ahmadreza; Esfahani, M. Reza
Abstract: In the present study, industrial wastes were used as a partial replacement for cement to form cement-based repair mortars, and the feasibility of using these mortars as the matrix in fiber reinforced cementitious matrix (FRCM) system for shear strengthening of reinforced concrete (RC) beam specimens was investigated. Accordingly, an experimental program comprising two parts was carried out. Firstly, the properties of the mortars were examined through compressive strength, tensile strength, sulfuric acid resistivity, and electrical resistivity tests. Finally, 6 shear-critical RC beam specimens were manufactured, two of which remained un-strengthened acting as control specimens. Two specimens were strengthened in shear by carbon fiber reinforced polymer (CFRP) strips and two specimens were strengthened by fiber reinforced cementitious matrix (FRCM) layers made with prepared mortars. The shear capacity of the specimens was measured through 3-point bending test. The parameters investigated in the beam specimens included the effect of shear strengthening system (FRP/FRCM) and shear span/depth ratio. It was shown that the specimens strengthened by the FRCM system made with waste materials had similar or slightly better performance compared to the FRP strengthened specimens.